1978
DOI: 10.3109/00498257809069587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of some Urinary Metabolites of Propantheline Bromide in Man

Abstract: The peak plasma concn. of total radioactivity occurred 6 h after a single oral dose of [carboxyl-14C; methyl-2H3] propantheline bromide was administered to a healthy man. At this time 10% of the dose was present in the total plasma volume. 2. A total of 71% dose of radioactivity was excreted in urine in 96 h after dosage, 59% dose being excreted in the first 24 h. About 5.3% of the orally administered propantheline bromide was excreted unchanged. 3. T.l.c. analysis and g.l.c.-mass spectrometry showed xanthanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…The urinary excretion of some 3 to 4% of the orally administered propantheline bromide unchanged is comparable with the values of 1 to 10% reported in studies using the radiolabelled compound (1,2).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The urinary excretion of some 3 to 4% of the orally administered propantheline bromide unchanged is comparable with the values of 1 to 10% reported in studies using the radiolabelled compound (1,2).…”
Section: Discussionsupporting
confidence: 71%
“…The initial pharmacokinetic studies have shown that the intravenously administered drug is rapidly distributed and eliminated in man with an elimination half-life of 1 to 3 hours, and that metabolism is the major elimination route (4). The urinary excretion data were comparable to the results obtained by radioisotope techniques (1,2), with some 17.3% and 1.08% of the drug excreted unchanged after i.v, and oral administration respectively.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…This compound appears to undergo appreciable metabolism in man, even after intravenous administration (Beermann, Hellstrom & Rosen, 1972). Following oral administration of "4C-labelled propantheline bromide to normal men some 70% of the administered radioactivity was excreted in urine, but the majority of this was present as metabolites of the drug (Beermann et al, 1972;Vose, Prout, Haskins, Ford, Palmer & Tidd, 1978). These metabolites included xanthanoic acid, hydroxyxanthanoic acid, hydroxypropantheline, and a number of conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…PB is extensively metabolized in man, with only 17 to 20% of an i.v. dose and less than fO% of an oral dose excreted unchanged in urine (I, 3,4). The low oral absorption and extensive metabolism of PB have increased the'difficulty of its analysis in biological fluids, and pharmacological responses have been measured in studies of its availability (5,6,7).…”
Section: Introductionmentioning
confidence: 99%